Why the concept of private demand for innovations should be understand: the case of ex-YU countries - Stojanovska, Slagjana (Mednarodno inovativno poslovanje, 2018)
This paper aims to provide a comparative analysis of private demand for innovation in the context of the ex-YU countries such as Slovenia, Croatia, Serbia and Macedonia from 2011 to 2016. One key variable for the importance of demand for innovation is the buyer sophistication. This signals the ability of buyers to select products and services based on performance rather than price and to bear the cost of products at the beginning of the life cycle. The companies that face a sophisticated domestic market are likely to sell high quality products and a close proximity to such consumers should to enables the company to better understand the needs and desires of the customers and how they perceive the value of the product. For cultural or historical reasons, buyers may be more demanding in some countries than in others. Hence, "ur start point is that "higher degrees of buyer sophistication can to explain higher shares of innovative sales' (Hollanders and Es-Sadki, 2017, p. 42) and opposite "lower shares of innovative sales could to explain lower degrees of buyer sophistication" in the above countries.
Keywords: buyer sophistication; innovations; inovacije; prefinjenost kupcev; private demand; prodaja; sales; value; vrednost; zasebno povpraševanje